Optimal Sizing and Economical Analysis of PV-Wind Hybrid Power System for Water Irrigation using Genetic Algorithm - Ninet Mohamed Ahmed; Hanaa Mohamed Farghally; Faten Hosney Fahmy (International Journal of Electrical and Computer Engineering (IJECE), 2017)
In the present study three renewable power systems are proposed to select the most optimum one for powering an irrigation pumping system and a farmer’s house in two different locations in Sinai, Egypt. Abu-Rudies in south Sinai and El-Arish in north Sinai are the two selected locations. The three suggested power systems are; standalone photovoltaic (PV) system, standalone wind system and standalone PV-wind hybrid system. HOGA (Hybrid Optimization by Genetic Algorithms) simulation software tool based on genetic algorithm (GA) is used for sizing, optimization and economical evaluation of three suggested renewable power systems. Optimization of the powersystem is based on the components sizing and the operational strategy.  The calculated maximum amount of water required for irrigating ten acres of olive per day is 170 m3. In terms of cost effectiveness, the optimal configurations are the hybrid PV-wind system and the standalone PV system for Abu-Rudies and El-Arish locations respectively. These systems are the most suitable than the others for the selected sites metrological data and the suggested electrical load